Spotify, an Example of Convergence in Digital Music and its Impact on Tastes: An Integrative Review - Beltrán Peña, Juan Sebastián (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
“Spotify, Digital Music and its Impact on Musical Tastes” is born from the curiosity that revolves around music and its different formats, with the aim of exposing that the deepening of academic literature on Spotify and digital music is taking its first steps. This idea is based on the question: “To what extent is academic literature around the convergence of digital music and the impact of Spotify today?” To answer it, we use the methodological model of an integrative review and the analysis of the sample under the criterion of the relationship between its main concepts.